Regulatory B lymphocyte functions should be considered in chronic lymphocytic leukemia. (3rd May 2016) - Mohr, Audrey; Renaudineau, Yves; Bagacean, Cristina; Pers, Jacques-Olivier; Jamin, Christophe; Bordron, Anne
ABSTRACT: Chronic lymphocytic leukemia (CLL) is characterized by an abnormal expansion of mature B cells in the bone marrow and their accumulation in blood and secondary lymphoid organs. Tumor CLL cells share expression of various surface molecules with many subsets of B cells and have several common characteristics with regulatory B cells (B regs). However, the identification of B regs and their role in CLL remain elusive. The aim of this review is to summarize recent works regarding the regulatory and phenotypic characteristic of B regs and their associated effects on the immune system. It is also meant to highlight their potential importance with regards to the immunotherapeutic response.